EFEKTIVITAS EKSTRAK DAUN CEREMAI (PHYLLANTHUS ACIDUS) TERHADAP MORTALITAS LARVA AEDES AEGYPTI - CATUR PRATIWI, YULIDA (Universitas Negeri Surabaya, 2013)
Aedes aegypti is an arbovirus disease vector i.e. dengue hemorrhagic fever, yellow fever, encephalitis, and chikungunya. One of the vector controlling is using botanical larvicide from Phyllanthus acidus leaves. This research aimed to describe the secondary metabolite of Phyllanthus acidus leaves extract; to describe the effect of Phyllanthus acidus leaves extract on the mortality of Aedes aegypti larvae; and to determine the lethal concentration of Phyllanthus acidus leaves extract for 50% and 90% mortality (LC50 and LC90) at 24, 48, and 72 hours after treatment. It was laboratory experimental by completely random design. The experimental object was 3rd instars of Aedes aegypti larvae that got into liquid of Phyllanthus acidus leaves extract: 0.4%; 0.6%; 0.8%; 1.0%; 1.2%; and 0% as control. There were 4 replications and every unit treatments consisted of 20 larvae. Mortality counting was held every 24 hours for 3 days, and then it was analyzed by One Way ANOVA, Tukey (HSD), and Probit. The phytochemical testing showed that Phyllanthus acidus leaves extract contain of flavonoid, tannin, and saponin. Phyllanthus acidus leaves extract significantly affected on the mortality of Aedes aegypti larvae at 24, 48, and 72 hours after treatment. LC50 and LC90 were: 0.505% and 0.922% at 24 hours after treatment; 0.432% and 0.732% at 48 hours after treatment; 0.421% and 0.682% at 72 hours after treatment.   Key words: Aedes aegypti; Phyllanthus acidus leaves; mortality of larvae; LC50; LC90